Applications of the hormesis concept in soil and environmental health research - Evgenios Agathokleous; Chen-Jing Liu; Edward J. Calabrese (Elsevier, 2023)
Hormesis refers to positive biological effects caused by exposure to low doses of a stressor known to be toxic at higher doses. These effects include an enhanced defense system and stimulated plant/microorganism growth and reproduction. Hormesis has emerged as a fundamental concept with broad relevance to the field of soil and environmental health. Its utilization in evaluating environmental effects and ecotoxicity can reduce uncertainties introduced by extrapolating from high to low doses of pollutants. Similarly, its consideration in risk assessment can help tackle toxicity risks imposed by chemical mixtures. Further, it can maximize the effectiveness of novel agrochemicals applied at the lowest possible concentration, thus reducing their ecological and human risks. Hormesis-based interventions, such as plant priming and stimulation of beneficial insects and waste-degrading microbes, can further reduce agrochemical loads into the environment, thereby enhancing plant and soil health. Inclusion of hormesis in strategies to control harmful organisms, such as pests, pathogenic microbes and harmful algal bloom organisms, can aid in combating chemical resistance. Hormesis-inclusive studies also provide useful information regarding suitable pollutant tolerance levels for microorganisms and plants during bioremediation and phytoremediation, thus enhancing environmental remediation. In sum, hormesis is highly relevant and offers numerous potential applications in soil and environmental health research.